2017
DOI: 10.1111/jnp.12133
|View full text |Cite
|
Sign up to set email alerts
|

Action observation produces motor resonance in Parkinson's disease

Abstract: Observation of movement activates the observer's own motor system, influencing the performance of actions and facilitating social interaction. This motor resonance is demonstrated behaviourally through visuomotor priming, whereby response latencies are influenced by the compatibility between an intended action and an observed (task‐irrelevant) action. The impact of movement disorders such as Parkinson's disease (PD) on motor resonance is unclear, as previous studies of visuomotor priming have not separated imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

8
2

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…The characteristics of AOT stimuli vary across the included studies with some research suggesting an association between features of video-clips and AOT efficacy (11). Studies have described additional benefits when AOT is associated with motor imagery in both healthy subjects and patients with neurological disorders (40)(41)(42)(43). However, none of the studies administering AOT in subjects with PD took into account the association between AOT and motor imagery.…”
Section: Characteristics Of the Stimulimentioning
confidence: 99%
“…The characteristics of AOT stimuli vary across the included studies with some research suggesting an association between features of video-clips and AOT efficacy (11). Studies have described additional benefits when AOT is associated with motor imagery in both healthy subjects and patients with neurological disorders (40)(41)(42)(43). However, none of the studies administering AOT in subjects with PD took into account the association between AOT and motor imagery.…”
Section: Characteristics Of the Stimulimentioning
confidence: 99%
“…AO and MI have shown promising effects in neurorehabilitation [24][25][26]. In a small number of laboratory studies in people with PD, AO influenced movement speed and timing in reaching [27] and finger-tapping [28] tasks, as well as hand movement amplitude [29], and preserved motor resonance for incidentally observed hand actions has been found in PD [30]. People with PD also report similar vividness of MI to healthy controls; however, like their actual movements, their imagery may be slowed [31], and compensatory mechanisms may be involved [32,33].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, MI training is recommended in rehabilitation guidelines from the American Stroke Association [31]. Although a smaller number of studies have investigated AO and MI in PD, AO has been found to influence movement speed and timing in reaching [32] and finger-tapping [33] tasks, as well as hand movement amplitude [34], and people with PD have shown preserved motor resonance for incidentally-observed hand actions [35]. People with PD also report similar vividness of MI to healthy controls; however, like their actual 3 movements their imagery may be slowed [36], and compensatory mechanisms may be involved, such as a greater reliance on visual processes [37,38].…”
Section: Action Observation and Motor Imagery As Tools To Facilitate mentioning
confidence: 99%